Inside BAR (The Biblical archaeology review, 1980)
Charles Kennedy, Professor of Religion at Virginia Polytechnic Institute and State University in Blacksburg, Virginia, is a noted authority on the catacombs of Rome. This expertise may or may not explain the fact that Kennedy’s students at Virginia Tech sometimes complain that his lectures leave them in the dark. In response to their complaints, […]